A THE EFFECT OF YOGA AND MINDFULNESS MEDITATION ON ALPHA-AMYLASE LEVEL - Brigitta Brigitta; Latisha Lubianca; Jessica Jessica; Tania Rosa; Eka Diah; Nila Wahyuni; I Putu Gede Adiatmika (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2022)
In recent years, a lot of behavioral studies have shown that physical exercise and yoga have a positive impact on one’s physical and mental health. Yoga, which is increasingly used in the clinical setting of various mental and physical health problems, especially stress-related illnesses and concerns, has shown promising effects. This research is focused on evaluation of the stress levels in one’s body by measuring the levels of salivary stress marker alpha-amylase in accordance with yoga and mindful meditation. This study will focus on literature review using Boolean operator with databases from ScienceDirect, Pubmed, and Cochrane.